Normative-Consequential Structures and Moral Dilemma Limitations in Islamic Social Ethics: A Developmental Analysis of Phase F Instructional Materials - Supriyanto, Supriyanto; Al-Aqsha, Andi Qadri (HEUTAGOGIA: Journal of Islamic Education, 2026)
This research identifies the normative-consequential structures and the scarcity of moral dilemmas in Phase F Islamic Social Ethics materials, analyzed through Piagetian and Kohlbergian developmental frameworks. Utilizing a qualitative content analysis approach, the study evaluated the 2021 Grade XI PAI textbook and official curriculum standards, coding 508 meaning units based on five distinct moral reasoning indicators. Results indicate that instructional content is heavily weighted toward the "Understanding of Social Rules" (48.03%) and "Consideration of Social Consequences" (35.04%). In contrast, the "Reflection on Moral Dilemmas" indicator is nearly absent (0.79%), highlighting a significant gap in facilitating the transition from heteronomous to autonomous moral stages. The findings suggest that current materials reinforce conventional moral adherence but lack the reflective-dialogic depth necessary to foster post-conventional reasoning among adolescents. A primary limitation of this study lies in its focus on document analysis, which precludes an assessment of live classroom dynamics and student receptivity. It is recommended that future inquiries employ mixed-methods designs to evaluate teacher-led interventions that utilize open-ended ethical conflicts to stimulate higher-order moral cognition.